ANALYSIS OF THE INCIDENCE OF RHEUMATIC DISEASES IN THE ARKHANGELSK REGION: TRENDS IN THE 2010–2015 STATISTICAL CHARACTERISTICS - L. Titova V.; M. Makarova V.; Л. Титова В.; М. Макарова В. (Rheumatology Science and Practice, 2017)
Objective: to investigate the incidence of acute rheumatic fever (ARF), chronic rheumatic heart disease (CRHD), musculoskeletal diseases (MSD), and connective tissue diseases in the pediatric and adult populations of the Arkhangelsk Region (AR) in comparison with the data on Russia and the North-Western Federal District (NWFD) in 2010–2015.Subjects and methods. The total and primary incidence rates of ARF, CRHD, and MSD were analyzed in the pediatric and adult populations of these regions in 2010–2015.Results and discussion. Among the adult population of AR, the total incidence of ARF was low (7 cases in 2010 and none in 2015), which is comparable with the data in the whole of Russia. No recurrences of ARF were registered in the AR. Among the adult population of AR, the total incidence of CRHD fell by 28% in 2010 to 2015. The similar trend was also observed in the whole of Russia. Patients newly diagnosed with CRHD decreased by 65% in the AR. There was a 14% increase in the total incidence of MSD among the adult population of AR and an 11% decrease in its primary incidence. Since 2010, the total incidence of rheumatoid arthritis (RA), osteoarthritis, spondylopathies (SP), osteoporosis (OP), and systemic connective tissue diseases rose in the AR. There were 22 and 140% increases in the incidence of RA and SP, respectively; the number of reactive arthritis cases decreased by 17.2% in the adults and increased by 7% in the children. This trend in the adults is seen of the whole of Russia (an 8% decrease), although the latter in the AR is not comparable to the All-Russian measures. In the AR, the incidence of OP remains low (50 and 73 per 100,000 population in 2010 and 2015, respectively); this is noted to increase by 46% in the past 5 years; the similar trend was observed in both the whole of Russia and NWFD (7.8 and 8.3%, respectively). Цель исследования – изучение заболеваемости детского и взрослого населения острой ревматической лихорадкой (ОРЛ) и хронической ревматической болезнью сердца (ХРБС), болезнями костно-мышечной системы (БКМС) и соединительной ткани в Архангельской области (АО) в сравнении с данными по России и Северо-Западному федеральному округу (СЗФО) за 2010–2015 гг.Материал и методы. Проведен анализ общей и первичной заболеваемости ОРЛ, ХРБС и БКМС детского и взрослого населения указанных регионов за 2010–2015 гг.Результаты и обсуждение. Среди взрослого населения АО общая заболеваемость ОРЛ низкая (в 2010 г. – 7 больных, в 2015 г. – ни одного пациента), что сопоставимо с данными в целом по России. Рецидивы ОРЛ в АО не зарегистрированы. Общая заболеваемость ХРБС среди взрослого населения АО в период с 2010 по 2015 г. снизилась на 28%. Подобная тенденция отмечается и в целом по России. Число впервые установленных диагнозов ХРБС в АО уменьшилось на 65%. Отмечен рост общей заболеваемости БКМС среди взрослого населения АО на 14%, первичная заболеваемость снизилась на 11%. С 2010 г. в АО произошел рост общей заболеваемости ревматоидным артритом (РА), остеоартритом, спондилопатиями (СП), остеопорозом (ОП), системными заболеваниями соединительной ткани. Выявлен рост заболеваемости РА на 22%, СП – на 140%, число случаев реактивных артритов уменьшилось на 17,2% у взрослых, у детей оно увеличилось на 7%. Подобная тенденция у взрослых отмечается и в целом по России (снижение на 8%), хотя уровень снижения в АО не сопоставим с общероссийскими показателями. Заболеваемость ОП в АО сохраняется на низких значениях (2010 г. – 50; 2015 г. – 73 на 100 тыс. населения), за последние 5 лет отмечается ее нарастание на 46%; аналогичная тенденция отмечена как в целом по России, так и в СЗФО (7,8 и 8,3% соответственно).